Lipid Homeostasis and Its Links With Protein Misfolding Diseases - Vendruscolo, Michele (Frontiers in Molecular Neuroscience, 2022)
The maintenance of lipid homeostasis is essential for the normal functioning of living organisms. Alterations of the lipid homeostasis system remodel the composition of the lipidome, potentially leading to the formation of toxic lipid species. In turn, lipidome changes can affect the protein homeostasis system by causing perturbations that elicit protein condensation phenomena such as protein liquid-liquid phase separation and protein aggregation. Lipids can also be more directly involved the formation of aberrant condensed states of proteins by facilitating the early events that initiate these processes and by stabilising the condensed states themselves. These observations suggest that lipid-induced toxicity can contribute to protein misfolding diseases, including Alzheimer’s and Parkinson’s diseases. According to this view, an impairment of the lipid homeostasis system generates toxic states of lipids that disturb the protein homeostasis system and promote the formation of toxic states of proteins.